Process feasibility study of energy integrated distillation columns sequence (EIDCS) for NGL separation process - Munawar Zaman Shahruddin; Muhammad Hanis Fikri Mohamad Uzuman; Rohani Mohd Zin; Tengku Amran Tengku Mohd; Mohd Kamaruddin Abd. Hamid; Renanto Handogo (Semarak Ilmu Publishing, 2025)
Distillation is a well-known process in the chemical and petrochemical industries for performing intended separation tasks. However, a common problem with this process is the high energy consumption of multicomponent distillation systems. Thus, the objective of this paper is to produce a distillation column sequence with the lowest energy requirement. The solution is to use the sequencing method of Driving Force with the help from Pinch Analysis method for maximum heat recovery, widely known as the Energy Integrated Distillation Columns Sequence (EIDCS). The distillation process involves eight natural gas liquids (NGL) components: methane, ethane, propane, i-butane, n-butane, n- pentane, n-hexane, and n-heptane. In the first step, the best sequence is determined by plotting the driving force graph of all components. Two types of simulations are carried out for both direct sequence and driving force sequence, including shortcut and rigorous simulations using Aspen HYSYS V10 software. Then, further potential energy savings can be achieved using Thermal Pinch Analysis. Data from the simulations are extracted for pinch analysis at a fixed ΔTmin value of 10°C using the Problem Table Algorithm (PTA) approach based on total load, heating load, and cooling load. The grid diagram of the heat exchanger network for the best sequence is then constructed. The results indicate that the driving force method provides a better sequence with lower energy requirements for distillation compared to the direct sequence. Moreover, the use of pinch technology proves to be effective as it enhances energy savings for the distillation process. The driving force sequence with pinch analysis recorded energy savings of 35.48% in heating load, 41.40% in cooling load, and 38.21% in total load. In conclusion, the driving force method can be considered one of the successful approaches for determining the best sequence, and pinch analysis for maximum heat recovery.